The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.3354/ab00141
|View full text |Cite
|
Sign up to set email alerts
|

Calcium influence on phosphorus regulation in Daphnia magna: implications for phosphorus cycling

Abstract: We examined the influence of environmental calcium on phosphorus biokinetics and regulation in Daphnia magna. When the Ca concentration in culturing media increased from 0.5 to 200 mg l -1 , the specific P content of D. magna feeding on P-sufficient algae decreased significantly from 1.43 to 1.05% of dry weight. There was a significant negative relationship between the specific Ca and P contents (% dry wt) of daphnids. However, measured biokinetic parameters, including the assimilation efficiency (AE) of dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Elemental limitation resulted in large changes in consumer body stoichiometry and growth rates in animals grown across nutrient gradients. Our results confirm previous daphnid studies showing changes in body Ca and P content in animals grown under low nutrient supplies (He and Wang ; Tan and Wang ). However, we found that dietary P was the most significant variable controlling daphnid elemental content, explaining the majority of variation in consumer body Ca : P ratios.…”
Section: Discussionsupporting
confidence: 92%
“…Elemental limitation resulted in large changes in consumer body stoichiometry and growth rates in animals grown across nutrient gradients. Our results confirm previous daphnid studies showing changes in body Ca and P content in animals grown under low nutrient supplies (He and Wang ; Tan and Wang ). However, we found that dietary P was the most significant variable controlling daphnid elemental content, explaining the majority of variation in consumer body Ca : P ratios.…”
Section: Discussionsupporting
confidence: 92%
“…The medium was renewed every 2 d. The green alga C. reinhardtii was added as food at the dose of 1.0-2.5 3 10 6 cells individual 21 d 21 , depending on the cladoceran species and life stage of the cladocerans. The food abundance level was considered enough to ensure the optimal growth of these four species because 10 6 cells individual 21 d 21 was enough for the healthy growth of a larger species, D. magna (Tan and Wang 2009a).…”
Section: Methodsmentioning
confidence: 99%
“…are recognized as having higher Ca content than the nondaphnid cladocerans (Waervå gen et al 2002;Jeziorski and Yan 2006), and counterintuitively, smaller Daphnia species have lower Ca content than larger sized daphnids, despite their higher surface-to-volume ratio (Waervå gen et al 2002). In Daphnia magna, the differences in Ca content between juveniles and adults or among populations cultured in different Ca environments were successfully explained by the physiologically based biokinetic parameters (e.g., influx rate, J, and efflux rate constant, k e , of Ca [Tan and Wang 2009b]). Specifically, a higher Ca content originated from a higher J or a lower k e of Ca, or both.…”
mentioning
confidence: 99%
“…Body P content is not a static, species-specific trait. Instead, body P content is a property which varies as a function of the environment, maintenance costs, growth, C availability, food C : P and the degree of stoichiometric homeostasis (Kyle et al 2006;Shimizu & Urabe 2008;Tan & Wang 2009). The degree of stoichiometric homeostasis is defined as resistance to change of animal stoichiometry (e.g.…”
Section: U N C E R T a I N T Y R E L A T E D T O S T O I C H I O M E mentioning
confidence: 99%